Impact of IgG response to malaria-specific antigens and immunity against malaria in pre-school children in Ghana. A cluster randomized, placebo-controlled trial. - Samuel Kofi Tchum; Samuel Asamoah Sakyi; Bright Adu; Fareed Arthur; Felix Boakye Oppong; Francis Dzabeng; Benjamin Amoani; Thomas Gyan; Kwaku Poku-Asante (PLoS ONE, 2021)
Background Iron fortification and micronutrient initiatives, specifically, vitamin A, and zinc supplementation are the most cost-effective developmental strategies against malnutrition and health emergencies in pre-school children. Iron-deficiency among pre-school children have been documented, however, studies evaluating the impact of immunoglobulin G (IgG) isotype responses among iron-fortified pre-school children in malaria endemic communities has not been assessed. We evaluated the impact of iron fortification on the IgG responses to GLURP R0, GLURP R2 and MSP3 FVO malaria-specific antigens among pre-school children in malaria endemic areas. Methods This community-based, placebo-controlled, double-blinded, cluster-randomized trial study was conducted in Wenchi Municipal and Tain District of Bono Region. The trial was registered at ClinicalTrials.gov-registered trial (Identifier: NCT01001871). Ethical approval was obtained and informed consent were sought from each participant parents/guardian. For the current objective, 871 children aged 6-35 months were screened, from which 435 children received semi-liquid home-made meals mixed with 12.5 mg of iron daily (intervention group), and 436 received micronutrient powder without iron (placebo group) for 5 months. Standardized clinical and epidemiological questionnaires were administered and blood samples taken to measure IgG responses to GLURP R0, GLURP R2 and MSP3 FVO recombinant antigens using the Afro Immunoassay (AIA) protocol. Results Baseline anthropometry, malaria diagnosis, anaemia and iron status, demographic features and dietary intake were identical among the groups (p > 0.05). After the intervention, there was no significant difference in the IgG response against GLUP R0, GLUP R2 and MSP3 FVO between the iron-containing micronutrient and placebo groups (p > 0.05). The iron-containing micronutrient powder group who were iron-sufficient or iron replete had significantly higher IgG response to GLURP R0 and GLURP R2 compared to iron-deficient and iron-deficiency anaemia in the same group (p < 0.05). The IgG responses to all the three malaria specific antigens were low among children without malaria episode but high among those with two and four episodes due to exposure differences. Conclusion Iron fortification did not influence antibody response against endogenous malaria specific antigens among pre-school children in malaria endemic areas, however, IgG response to malaria specific antigens were high among children with sufficient iron status.